2015
DOI: 10.1021/acs.langmuir.5b02224
|View full text |Cite
|
Sign up to set email alerts
|

Three-Phase Coexistence in Colloidal Rod–Plate Mixtures

Abstract: Aqueous suspensions of clay particles, such as montmorillonite (MMT) platelets and sepiolite (Sep) rods, tend to form gels at concentrations around 1 vol %. For Sep rods, adsorbing sodium polyacrylate to the surface allows for an isotropic-nematic phase separation to be seen instead. Here, MMT is added to such Sep suspensions, resulting in a complex phase behavior. Across a range of clay concentrations, separation into three phases is observed: a lower, nematic phase dominated by Sep rods, a MMT-rich middle la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 41 publications
0
19
0
Order By: Relevance
“…Although no biaxial nematic phase appeared in this system, the phase diagram shows up to four distinct liquid-crystalline phases, including several different rod-rich and disk-rich nematic phases. Other examples are mixtures of sepiolite nanorods a few microns long with montmorillonite nanosheets about one micron in diameter 26 . This system has an unusual phase diagram with regions where an isotropic phase coexists with two nematic phases differing by their compositions.…”
Section: Introductionmentioning
confidence: 99%
“…Although no biaxial nematic phase appeared in this system, the phase diagram shows up to four distinct liquid-crystalline phases, including several different rod-rich and disk-rich nematic phases. Other examples are mixtures of sepiolite nanorods a few microns long with montmorillonite nanosheets about one micron in diameter 26 . This system has an unusual phase diagram with regions where an isotropic phase coexists with two nematic phases differing by their compositions.…”
Section: Introductionmentioning
confidence: 99%
“…Woolston and Duijneveldt found that combining montmorillonite (MMT) nanoplatelets with sepiolite (Sep) nanocylinders also showed complex phase behavior [128]. The aqueous MMT alone formed a gel, and aqueous Sep formed a nematic, but the addition of Sep to MMT could result in three-phase coexistence where the bottom layer consisted of a nematic Sep cylinder-rich phase, the middle layer consisted of an MMT platelet-rich phase, and the top layer was a dilute isotropic layer [128]. For all MMT concentrations above 1 vol%, however, the system gelled and the MMT concentration required for gelation decreased as the Sep concentration was increased to 4 vol%.…”
Section: Nanoplatelets and Nanocylinders (2d-1d)mentioning
confidence: 99%
“…Prominent examples are the ordered structures found in colloidal systems 4 such as colloid crystals and colloidal LCs. 5 Further, combination of components with dissimilar morphologies such as rod/plate, 6 rod/sphere, 7 plate/sphere, 8 nanosheet/rod, 9 nanosheet/nanosheet, 10 and plate/polymer 11 types of particles also facilitates formation of variety of well-ordered structures. Thus, complexity of the system is a key to develop highly organized and hierarchical structures.…”
Section: Introductionmentioning
confidence: 99%